Sputter deposition and characterization of metal sandwiched indium tin oxide/silicon for solar cell application - Kabiru Isiyaku, Aliyu (2020)
For the past four decades, indium tin oxide (ITO) thin films have been widely used as transparent and conductive contact layer in several optoelectronic applications due to their high optical transmission and good electrical conductivity. Because of the rapid advancement of optoelectronic devices, new ITO design and structures are required to improve their performance for use in advanced applications. In this work, multilayer films structures of ITO/Al-Ag/ITO (IAAI) on n-type Si and ITO/Al-Cu/ITO (IACI) on p-type Si were prepared at room temperature by radio frequency (RF) and direct current (DC) magnetron sputtering technique. The microstructural, topological, morphological, optical and electrical properties of the prepared films were investigated after undergoing post-annealing treatment in a range of 300-600oC in air. X-ray diffraction analysis of the as-deposited IAAI and IACI films show an amorphous structure with low intensity and broad diffraction Ag peak at (111) appearing on IAAI film indicating the presence of Ag film in a crystalline phase. The presence of In2O3 crystals peaks with Ag (111) and Al (200) for IAAI films and Cu (111) for IACI films were observed after post-annealing treatment indicating a crystalline improvement in the films. Topological analysis reveals an improved smooth surface topology and grain size with increasing post annealing temperature. The IAAI and IACI films showed better and improved microstructure at 500oC and 600oC respectively. The optical analysis shows a significant increase in transmittance with increasing annealing temperature. High optical transmittance of 91.01 % and 88.70 % for IAAI and IACI films annealed at 500oC and 600oC were obtained. The lowest sheet resistance of 3.81 Ω/sq by IAAI film annealed at 500oC and 3.26 Ω/sq by IACI film annealed at 600oC were obtained. Current-voltage characteristics analysis indicates a superior ohmic behaviour for IAAI films deposited on n-type Si and rectifying contacts on p-type Si for IACI films after post-annealing treatment making them an excellent IAAI/n-Si and IACI/p-Si contacts candidates for Si solar cells application.